Distribution and conservation of threatened gymnosperms in China - Dan Xie; Liu, Xin-Quan; Chen, Ya-Xing; Jiao, Dan; Lou, Jia-Xin; Qiu, Xiu-Fei; Xu, Wei-Hua; Wang, Zhi-Heng; Ran, Jin-Hua; Wang, Xiao-Quan (Global Ecology and Conservation, 2021)
China is one of the diversity centers of gymnosperms. Nearly one-fifth (195 species) of gymnosperms are located in China, but 69 species are threatened. To date, the conservation status of gymnosperms, especially threatened gymnosperms in China, remains largely unknown, which seriously restricts the comprehensive protection of gymnosperms. Understanding the distribution pattern of species richness and exploring the relationships between species richness and environmental factors are key steps for their protection. In this study, we first constructed a database for the 69 threatened species of gymnosperms with 13 270 distribution records. It is found that 31 of the grid cells (50 × 50 km) cover all threatened gymnosperm species in China, and the grid cells of threatened gymnosperms are mainly distributed in the southern area of the Yellow River, with a distribution center in the Western Sichuan Plateau. Then, we evaluated the conservation status of threatened gymnosperms, and the results indicate that 9 (13%) threatened gymnosperms are distributed outside of nature reserves. Therefore, there are still conservation gaps in the protection of threatened gymnosperms in China. We should give more attention to unprotected threatened gymnosperms and conduct taxonomic studies on the species without detailed distribution records. Finally, conservation priority areas and priority conservation levels of threatened gymnosperms in China were proposed. The Western Sichuan Plateau is the most important conservation priority area of threatened gymnosperms. This study will shed light on plant protection and forest management in China.
Keywords: Conservation gap; Distribution pattern; Gymnosperm; Nature reserve; species richness